Adolescent use of the combined oral contraceptive pill: a retrospective observational study. Issue 9 (26th April 2005) - Krishnamoorthy, N; Ekins-Daukes, S; Simpson, C R; Milne, R M; Helms, P J; McLay, J S
Abstract : Aims: To determine the extent of combined oral contraceptive use by girls aged 10–16 years in Scotland. Methods: Assessment of combined oral contraceptive prescribing in 35 414 girls for the year 1 November 1999–31 October 2000 from data retrieved from 161 primary care practices taking part in the Scottish Programme for Improving Clinical Effectiveness in Primary Care, and from national aggregated data from family planning clinics. Results: During the study period the oral contraceptive pill (OCP) was prescribed by a primary care physician to 1531 girls (4.3%) aged 10–16 years. The age specific prevalence rates per 1000 girls registered with their family doctor rose from 0.9/1000 girls aged 12 years or younger, to 6.9, 30, 86.3, and 174.8/1000 for girls aged 13, 14, 15, and 16 years respectively. The overall prevalence of combined oral contraceptive prescribing by primary care physicians was 43.2/1000 girls aged 10–16 years. A further 1765 girls aged 13–16 years obtained a prescription for the OCP from a Scottish family planning clinic, giving an overall prevalence rate for family planning clinic prescribing of 8.0/1000 girls aged 10–16 years. Despite reportedly high levels of sexual activity and teenage pregnancy in this age group, these results confirm that OCP use is relatively low. Conclusions: The UK has the highest rate of teenage pregnancy in Western Europe, but despite the medical and social concerns about the sexual health of teenagers, the level of oral contraceptive use in this young age group remains low.